Values of Religious Moderation in the Novel "Kambing dan Hujan" by Mahfud Ikhwan. - Arafat, Muhammad Yasir Arafat; Fika Inama Sari (Moderatio: Jurnal Moderasi Beragama, 2025)
His research aims to analyze the values and indicators of religious moderation attitudes implicitly present in the Novel Kambing dan Hujan by Mahfud Ikhwan. Religious moderation is Clearly evident in this novel, as the conflicts portrayed arise from differences in religious beliefs within a village named Centong. This study employs qualitative research methodology with a content analysis approach, focusing specifically on the content of the novel. The findings indicate that the novel Kambing dan Hujan contains several values of religious moderation including Tawassuth, Tawazun, I'tidal, Tasamuh, Musawah, Syuro, Islah, and Awlawiyah. These values are highly relevant when applied within Indonesia's multicultural society to maintain harmonious living despite differences.